CBL-Interacting Protein Kinase OsCIPK18 Regulates the Response of Ammonium Toxicity in Rice Roots - Sun, Tong; Wang, Ting; Qiang, Yalin; Zhao, Gangqing; Yang, Jian; Zhong, Hua; Peng, Xiaojue; Yang, Jing; Li, Yangsheng (Frontiers in Plant Science, 2022)
Ammonium (NH4+) is one of the major nitrogen sources for plants. However, excessive ammonium can cause seriously harm to the growth and development of plants, i.e., ammonium toxicity. The primary regulatory mechanisms behind ammonium toxicity are still poorly characterized. In this study, we presented OsCIPK18, a CBL-interacting protein kinase, plays an important role in response to ammonium toxicity by comparative analysis of the physiological and whole transcriptome of the T-DNA insertion mutant (cipk18) and the wild-type (WT). Root biomass and length of cipk18 are less inhibited by excess NH4+ compared with WT, indicating increased resistance to ammonium toxicity. Transcriptome analysis reveals that OsCIPK18 affects the NH4+ uptake by regulating the expression of OsAMT1;2 and other NH4+ transporters, but does not affect ammonium assimilation. Differentially expressed genes induced by excess NH4+ in WT and cipk18 were associated with functions such as ion transport, metabolism, cell wall formation, phytohormones signaling, suggesting a fundamental role for OsCIPK18 in ammonium toxicity. We further identified a transcriptional regulatory network downstream of OsCIPK18 under NH4+ stress that is centred on several core transcription factors. Moreover, OsCIPK18 might function as a transmitter in the auxin and abscisic acid (ABA) signaling pathways affected by excess ammonium. These data allowed us to define an OsCIPK18-regulated/dependent transcriptomic network for response of ammonium toxicity and provide new insights into the mechanisms underlying ammonium toxicity.